EXPLORING THE MULTIFACETED RELATIONSHIP BETWEEN MALE PATTERN HAIR LOSS AND SYSTEMIC HEALTH: A COMPREHENSIVE REVIEW - Zaynutdinov Makhmudkhuja Azizovich; Don Andrey Nikolaevich (Web of Journals Publishing, 2024)
Male pattern hair loss (MPHL) is traditionally linked to genetic predisposition and elevated dihydrotestosterone (DHT) levels. However, recent research reveals its complex association with systemic health conditions, such as metabolic syndrome, cardiovascular diseases (CVD), and COVID-19 outcomes. Studies suggest that androgenetic alopecia (AGA), especially vertex pattern AGA, may serve as a marker for early atherosclerosis and be an independent risk factor for CVD and metabolic syndrome. Meta-analyses also indicate a possible correlation between vertex baldness and prostate cancer risk. Moreover, androgen-mediated mechanisms have been implicated in the severity and mortality of COVID-19, with elevated androgen activity promoting viral entry through proteins like TMPRSS2 and ACE2. This review evaluates the relationship between androgens, MPHL, and systemic health, highlighting the potential for anti-androgen therapies and TMPRSS2 inhibitors in addressing both cardiovascular and infectious diseases. Further investigation into the role of androgens in these contexts is critical for advancing therapeutic strategies.
Keywords: MPHL, DHT, Metabolic syndrome, CVD, AGA, Vertex AGA, Atherosclerosis, CCA IMT, Prostate cancer, COVID-19, Androgens, TMPRSS2, ACE2, Inflammation, Anti-androgen therapy, TMPRSS2 inhibitors, Androgen deprivation, SARS-CoV-2.